On secularisation - structural, institutional and cultural determinants shaping individual secularisation - Müller, T (2012)
This thesis deals with the determinants and mechanisms of individual secularisation processes in a cross-national perspective. In this ‘collected volume’ of six stand-alone articles, I examine religious beliefs and behaviours as well as attitudes towards religion and politics, whereby the validity of the main theories of religious change (classical secularisation theory, existential security hypothesis, supply-side explanations, historical/cultural approaches and conflict theories) are put to an empirical test. The main conclusion is that the fundamental mechanisms suggested by secularisation theories are valid and that we can identify main determinants of religiosity worldwide. However, only a combination of existing approaches is capable of explaining a broad range of the phenomena observed. Chapter 1 (co-authored with Nan Dirk de Graaf and Peter Schmidt) deals with the fundamental mechanisms that facilitate the socialisation of religious beliefs. Under conditions of high inequality, religion acts as a source of social capital that benefits the religious socialisation of individuals outside of the family context. If levels of inequality fall, this ‘social value of religion’ is diminished and religious socialisation depends more strongly on parental efforts, thereby gradually leading to intergenerational secularisation. In Chapter 2 (co-authored with Anja Neundorf) we show that the state in Eastern Europe played a crucial role in de-establishing as well as re-establishing religious plausibility structures, which explains lower levels of religious belief in Cold War cohorts as well as the religious revival after the end of the Cold War. Chapters 3 and 4 examine the topic of religion and politics and the mechanisms behind the support for the 9/11 attacks in the Muslim world. Levels of existential security and income inequality have a strong impact on the preferences for religious politicians in a cross-sectional as well as in a longitudinal perspective. Moreover, religiosity and altruistic behaviour run the risk of being converted into pro-terrorist support under conditions of high levels of inequality and low development levels. The final two chapters show that –in a world-wide comparison development levels, inequality and the Socialist history of countries explain 75% of the variation in religiosity between countries. Furthermore, future developments in religious change will also be subject to changes in fertility. The main drivers of secularisation processes can be identified, but for the majority of the world population these conditions are not met at present, nor will they be met in the near future.